Assessment of temperature effects on body shape in Nile tilapia, Oreochromis niloticus juveniles using the truss network system - Mazaher Zamani-Faradonbe (University of Guilan, 2021)
Among the environmental factors, water temperature has a significant effect on many aspects of fish life. This study was carried out to examine effects of water temperature on body shape of Nile tilapia, Oreochromis niloticus during the early stages of life using truss network system. A total of 150 newly-born fry were reared in three temperature treatments (22, 28 and 34°C) for 40 days. At the end of experiment, the left side of the specimens was photographed. To achieve the body shape data, 13 landmark-points were digitized using tpsDig2 software. The extracted data were justified with generalized procrustes analysis, then the differences of body shape among groups were investigated using the principal component analysis (PCA), canonical variate analysis (CVA) and cluster analysis (CA). There were significant differences in body shape of the treatments. The results of CVA and CA indicated that one of the important factors in the aquatic habitats is water temperature that influences the body shape of the Nile tilapia during the first stages (larval and juvenile stages) of growth.